LGBT DALAM PERSPEKTIF HUKUM ISLAM - HASAN ZAINI (Institut Agama Islam Negeri Batusangkar, 2017)
Issues concerning with LGBT seem to be never lasting discussions. These are due to several disciplines, such as health, psychology, Islamic law, other related ones, that may give significant affects in the process making decisions concerning with the issues. Among the issues are dealing with positioning of LGBT either as nature or nurture, given or socially constructed, inherited or deviant, normal or diseased, and so forth. Such abnormal behaviors lead this group to the false understanding about sex in the wrong ways. This points out that the people that gets involved in LGBT fail to synchronize their desire and principles of life. This paper, therefore, aims at analyzing the perspectives of Islamic scholars of Islamic jurisprudence (fiqh) concerning with LGBT and the effects as well caused by